Consumerism Capitalist Perspective in Animation Film Sen To Chihiro No Kamikaushi By Hayao Miyazaki - Roberto Masami Prabowo (Humaniora, 2017)
One of the works of Studio Ghibli who directed by Hayao Miyazaki entitled Sen to Chihiro no Kamikakushi (千と千尋の神隠し) would be discussed in this research about the capitalist consumerism. The research method in this research was qualitative and descriptive analytical method. The results of this research will provide the new insights into the animation appreciation and the understanding of the implicit context in the story. People can understand the politic, economic, culture of Japanese after watching the work of Studio Ghibli. The author hopes that the results of this article will produce useful conclusions and will be used for the next study.